Synchronization of Traveling Waves in Memristively Coupled Ensembles of FitzHugh–Nagumo Neurons With Periodic Boundary Conditions - Korneev, I. A.; Ramazanov , I. R.; Semenov, V. V.; Slepnev, A. V.; Vadivasova, T. E. (Frontiers in Physics, 2022)
Synchronization of traveling waves in two rings of FitzHugh–Nagumo neurons is studied. Coupling between neurons within each ring is dissipative, while one between rings is memristive. Complete synchronization of waves in identical rings in the presence of an initial phase shift between wave processes and partial synchronization of waves in the case of different coupling strengths inside the rings are considered. The influence of the initial states of memristive coupling on the synchronization of wave processes in the case of memristors with an infinitely long memory and with the forgetting effect is investigated.